Perancangan Interior Tropical City Garden, Pusat Informasi dan Konservasi Bunga Tropis di Surabaya - Pauline Susanto (Intra, 2017)
Indonesia is an archipelagic country in which lives flora, fauna and microbes are very diverse with blessed as one of the most extensive and richest tropical forest of its biodiversity in the world. One of the diversity of Indonesia's natural resources is flora. Various kinds of flora and fauna that live in the forests of Indonesia. The diversity of flora that grows in Indonesia also has a myriad of diversity of benefits, such as foodstuffs, ingredients of medicine, handicraft materials, and the most important is the producer of oxygen and carbon dioxide absorber. However, the biological riches that exist in Indonesia's tropical forests have been damaged, threatened by sustainability and extinction.To conserve tropical forest flora in Indonesia, it is necessary to direct the community to get to know and move in preserving tropical flowers. Therefore, this problem requires a container that is not only for botanists to develop tropical flowers scientifically, but also requires a container that can reach the general public. In this case, educational place of recreation becomes one of the right solutions to see the progress of Surabaya.The design of the interior information center and conservation of tropical flowers has several goals to be achieved. Designers want to present a center of information and conservation of tropical flowers that become a container for botanists and lovers of flora to be able to cultivate tropical flowers. In addition to being a container, designers also want to bring the value of education, recreation, preservation and local content within this conservation center. The value of education and preservation is presented through sophisticated technology programs that are useful also to support the interior. Recreation is featured through existing support facilities to provide visitors with fun, and local content values are presented through Indonesia's tropical rainforest atmosphere. Visitors during the recreation at this conservation center, visitors can see and experiment directly on how the cultivation of tropical flowers. Beginning with direct experiments and some deeper introduction to tropical flowers, people can be interested in hopes and start moving to preserve tropical flowers.